Elevating student engagement and academic performance: A quantitative analysis of Python programming integration in the Merdeka Belajar curriculum - Rais, Damar; Zhao, Xuezhi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Python programming is widely employed in educational institutions worldwide. Within the Merdeka Belajar curriculum context, this programming is recognized as a suitable vehicle for mathematics instruction, significantly influencing students’ motivation and learning outcomes, particularly following periods of educational hiatus. This study examines the effectiveness of Python programming in promoting heightened learning outcomes by examining the intricate relationship between student motivation and learning. The study uses quantitative research methodologies to evaluate student learning facilitated through Python programming, encompassing problem-solving assessments and the administration of motivation questionnaires. By engaging in coding practices, students understand the symbols they manipulate, facilitating their ability to juxtapose data derived from mathematical modeling with the resultant programming output. When disparities arise, students are empowered to reassess their work, fostering a more profound comprehension of the subject matter. These exercises serve to augment students' capacity to retain and process information within memory. Furthermore, students demonstrate a favorable disposition, exhibiting persistence in resolving programming challenges by meticulously analyzing error outputs, particularly those pertaining to TypeErrors. Encouraging students to confront errors through thoroughly examining error output manifestations engenders an efficacious learning paradigm. This research proffers invaluable insights for educational institutions contemplating the integration of Python programming as an instructional adjunct.